PENERAPAN METODE LEARNING BY GAMES UNTUK PENINGKATAN KETERAMPILAN BINA DIRI SISWA PADA ANAK TUNAGRAHITA - Aisyah, Nur; Fajri, Zaenol; Faizah, Latifatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Self-help skills are important skills that must be possessed by children with disabilities to be able to live their daily lives independently. However, children with disabilities often experience difficulties in learning self-help skills because their characteristics are different from normal children. One of the efforts to improve self-help skills in children with disabilities is to apply the learning by games method. The learning by games method is a learning method that uses games as a learning medium. Games can make learning more fun and interesting for children with disabilities. In addition, games can also help children with disabilities to develop motor, cognitive, and social-emotional skills, which are needed to improve self-help skills.This study aims to examine the effectiveness of applying the learning by games method to improve self-help skills in students with disabilities. The research approach used is descriptive qualitative case study type. The data collection technique used is observation and documentation of SLBN Demung Besuki Situbondo directly, which begins with a general view of the interview data, and documentation while in the field. From this research, it is known that students with tunagrahita become easier to master the material without feeling depressed and bored because they use photo and video educational games, guest picture educational games, and puzzle educational games in improving self-help skills to make it easier for students with tunagrahita to take care of themselves in the form of thaharah / washing activities. As for its application, it requires teacher creativity in developing methods (photos and videos, guest pictures, puzzles, etc.) that are in accordance with the learning material so that students can more easily master and remember the material and feel happy and not burdened in learning.